Potential role of the gut microbiota of bumblebee Bombus pyrosoma in adaptation to high-altitude habitats - Zhang, Zhengyi; Guo, Yulong; Zhuang, Mingsheng; Liu, Fugang; Xia, Zhongyan; Zhang, Zhihao; Yang, Fan; Zeng, Huayan; Wu, Yueguo; Huang, Jiaxing; Li, Jilian (Frontiers in Microbiology, 2023)
The gut microbiota affects the health and overall fitness of bumblebees. It can enhance the host's ecological range by leveraging their metabolic capacities. However, the diversity of the gut microbiota and adaptive functional evolution in high-altitude regions remain unclear. To explore how the gut microbiota helps the host adapt to high-altitude environments, we analyzed the differences in diversity and function of the gut microbiota between high- and low-altitude regions through full-length 16S rRNA sequencing. Our results show that high-altitude regions have a lower abundance of Fructobacillus and Saccharibacter compared to low-altitude regions. Additionally, some individuals in low-altitude regions were invaded by opportunistic pathogens. The gut microbiota in high-altitude regions has a greater number of pathways involved in “Protein digestion and absorption” and “Biosynthesis of amino acids,” while fewer carbohydrate pathways are involved in “digestion and absorption” and “Salmonella infection.” Our finding suggests that plateau hosts typically reduce energy metabolism and enhance immunity in response to adverse environments. Correspondingly, the gut microbiota also makes changes, such as reducing carbohydrate degradation and increasing protein utilization in response to the host. Additionally, the gut microbiota regulates their abundance and function to help the host adapt to adverse high-altitude environments.